A Survey on Security Threats in Cloud Computing - Anusha, P; Maruthi, R (International Journal of Computer Sciences and Engineering, 2025)
Abstract— Cloud computing, also referred to as ‘on demand computing’, is a recent concept making waves in the IT industry. When compared to other specific, dedicated infrastructures in computing, cloud concept gives the advantage of reliability, quantifiability, cost- effectiveness and improved performance. It is easy and convenient to have network access to other shared configurable computing resources using this concept. Another advantage of the concept is that the resources can be utilized with increasing efficiency and minimum overhead efforts. Clouds can be used for services, solutions, and applications and also for storing large amount of data in different locations. Data is stored over a set of resources which are networked so that the data can be accessed through any other virtual system. The security and privacy issues associated with data management is reduced considerably using the cloud computing facility as the data centers are literally beyond the reach and control of users. Further, server breakdowns which normally affect data storage and use does not seem to affect the user in cloud computing. But this system has its own set of disadvantages. This work is an attempt discuss in detail cloud computing, its types and Network/security issues related to it. Networks structure faces some attacks that are denial off service attack, man in the middle attack, network sniffing, port scanning, SQL injection attack, cross site scripting. Security Issues that occur in Cloud Computing are XML signature element wrapping, Browser security, cloud malware injection attack, flooding attacks, data protection, insecure or incomplete data deletion, locks in.